Adverse orienting effects on visual working memory encoding and maintenance - Wang, Benchi (Psychon Bull Rev, 2016)
Visual working memory (VWM) representations can be strengthened by pre-cues presented before, and retro-cues presented after, the memory display, providing evidence that attentional orienting plays a role in memory encoding and maintenance. It is unknown whether attentional orienting to VWM stimuli can also have adverse effects (known as inhibition of return; IOR), as has been found for perceptual-cueing tasks. If so, this would provide further evidence for common attentional orienting mechanisms for mnemonic and perceptual representations. In Experiment 1, we used pre-cueing and demonstrated an increased encoding probability, but not precision, at short SOAs, but probability decreased at long SOAs, reminiscent of the classic IOR findings. In Experiment 2, we used retro-cueing and showed that it improved memory performance, unless attention was cued back to the center of the display by a second cue. In this case, the deleterious effects were on precision, indicating that the item was still retained, but its quality of representation suffered. Together, these results provide further evidence for universal spatial attentional mechanisms operating on perceptual as well as mnemonic representations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.3758/s13423-016-1205-4) contains supplementary material, which is available to authorized users.